Applications of kenaf-lignocellulosic fiber in polymer blends - Sarifuddin, Norshahida; Ismail, Hanafi (John Wiley & Sons, Inc., 2015)
Increasing environmental concerns have encouraged researchers worldwide to expand the invention of new materials that may replace conventional materials in various applications. Among the available lignocellulosic fibers, kenaf has recently emerged as an interesting reinforcing component for the development of natural fiber-based composites. The unique attributes of kenaf fibers, which are comparable to those of synthetic fibers, have driven the interest in exploiting their full potentiality in polymer composites and their diverse use. Yet, their compatibility with polymer matrices and inherent moisture absorption have become crucial concerns. Thus, this chapter addresses various aspects of kenaf fiber-reinforced polymer composites with respect to the characteristics of natural fibers. Also discussed are Malaysian kenaf, properties of kenafcomposites and possible treatments for fiber.